Inter- and intra-varietal clonal differences influence the aroma compound profiles of wines analyzed by GC–MS and GC-IMS - Huawei Chen; Shijian Bai; Bowei Yang; Ruihua Ren; Zizhu Tang; Zhenwen Zhang; Qingqing Zeng (Food Chemistry: X)
To investigate the impact of genetic factors on wine aroma, wines made from 22 clones of five grape varieties (Vitis vinifera L.) were used to analyze the volatile compounds by headspace solid phase microextraction gas chromatography mass spectrometer (HS-SPME-GC–MS) and headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS). Results showed that 52 and 49 aroma compounds were identified from 22 clones of wines by two technologies, respectively. Esters were the most abundant compounds, followed by alcohols and aldehydes. The aroma profiles demonstrated significant varietal and clonal diversity, the clones with the highest aroma compound content were CH VCR6, PN VCR20, CS VCR11, ML VCR101, and CF 678. Partial least squares discriminant analysis (PLS-DA) identified decanoic acid, 1-heptanol, diethyl succinate, ethyl octanoate, and octanal as key biomarkers for distinguishing 22 clones of wines. Our results revealed that white wine CH VCR6 and red wine CS VCR11 possessed the most complex aromas. These findings address the research gap concerning the genetic determinants of wine aroma, highlighting the significance of grape variety and clone selection in developing wines with desirable sensory attributes.